2015
DOI: 10.1039/c5mb00035a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoribulokinase from Chlamydomonas reinhardtii: a Benson–Calvin cycle enzyme enslaved to its cysteine residues

Abstract: Phosphoribulokinase (PRK) in the green alga Chlamydomonas reinhardtii is a finely regulated and well-studied enzyme of the Benson-Calvin cycle. PRK can form a complex with glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and the small chloroplast protein CP12. This study aimed to determine the molecular determinants on PRK involved in the complex and the mechanism of action of a recently described novel regulation of PRK that involves glutathionylation. A combination of mass spectrometry, mutagenesis and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 64 publications
(219 reference statements)
2
29
0
Order By: Relevance
“…In P. tricornutum, the formation of the regulatory complex GAPDH/PRK/CP12 has been already discarded [66], and there is no evidence of its formation in T. pseudonana. Moreover, it has been shown that the formation of this ternary complex requires the presence of two cysteine residues on PRK, that are absent in diatom PRK [67]. This suggests that regulation of GAPDH in these two diatoms relies on a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In P. tricornutum, the formation of the regulatory complex GAPDH/PRK/CP12 has been already discarded [66], and there is no evidence of its formation in T. pseudonana. Moreover, it has been shown that the formation of this ternary complex requires the presence of two cysteine residues on PRK, that are absent in diatom PRK [67]. This suggests that regulation of GAPDH in these two diatoms relies on a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Circular Dichroism : The GAPDH and MDH were diluted to 5 mg L −1 (35 and 75 × 10 −6 m for tetrameric GAPDH and dimeric MDH, respectively) and placed into a quartz cuvette with a final concentration at 8 or 80 mg L −1 AgNPs, or 8 mg L −1 Ag + , or 46 mg L −1 PVP. CD spectra from 190 to 250 nm were recorded on a spectropolarimeter (Jasco J‐1100, Jasco Analytical Instruments, Easton, Maryland) at 25 °C . For each spectrum, there were six successive scans.…”
Section: Methodsmentioning
confidence: 99%
“…CD spectra from 190 to 250 nm were recorded on a spectropolarimeter (Jasco J-1100, Jasco Analytical Instruments, Easton, Maryland) at 25 °C. [34] For each spectrum, there were six successive scans. The mean residue molar ellipticity θ (deg cm 2 dmol −1 ) was calculated from raw ellipticity E (mdeg) using Equation (1)…”
Section: Wwwsmall-journalcommentioning
confidence: 99%
“…The structural basis for this reversible inactivation is unknown. Sequences from -cyanobacteria, green algae and plants contain two pairs of conserved cysteine residues: one close to the presumed ATP-binding pocket and one close to the C-terminus (Thieulin-Pardo et al, 2015). Whereas thiol modification of Cys16 (but not the C16S mutation) of the N-terminal pair in PRK from green algae and plants strongly impairs the enzyme activity, modification or mutation of the C-terminal pair has no effect on enzyme activity in vitro (Milanez et al, 1991;Thieulin-Pardo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences from -cyanobacteria, green algae and plants contain two pairs of conserved cysteine residues: one close to the presumed ATP-binding pocket and one close to the C-terminus (Thieulin-Pardo et al, 2015). Whereas thiol modification of Cys16 (but not the C16S mutation) of the N-terminal pair in PRK from green algae and plants strongly impairs the enzyme activity, modification or mutation of the C-terminal pair has no effect on enzyme activity in vitro (Milanez et al, 1991;Thieulin-Pardo et al, 2015). Oxidized PRK from these organisms has been reported to become inactive (Porter et al, 1990) and to subsequently bind another CBB cycle enzyme, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), in a process which is mediated by the small intrinsically disordered protein CP12 in a redoxdependent manner (Clasper et al, 1991;Howard et al, 2008;Thieulin-Pardo et al, 2015;Avilan et al, 1997;Lebreton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%